A league of their own: Female soccer, male legacy and women's empowerment - Seo-Young Cho (Georg-August-Universität Göttingen, Ibero-America Institute for Economic Research (IAI), 2013)
This paper investigates whether male soccer tradition can predict the success of female soccer. Different from the existing literature, this paper utilizes panel data covering 175 countries during the 1991-2011 period, capturing country heterogeneity effects and time trends. An instrumental variable approach is further employed in order to identify causal relation. My findings do not support the widespread perception that male tradition determines female soccer attainments. On the other hand, my results indicate that women's empowerment can be a driving force for the success of female soccer.
Keywords: C33; J16; Z10; 330; female and male soccer; women's empowerment; panel analysis